IMPLEMENATASI PARON DI DESA GULUK-GULUK DALAM TINJAUAN FIKIH EMPAT MAZHAB - Syahadatina, Dini; Anwar, Moch Khoirul (Universitas Negeri Surabaya, 2020)
Indonesia has ample land and has abundant biodiversity so that Indonesia is called an agrarian country, Indonesian people have a livelihood in agriculture, there are several kinds of cooperation in the agricultural sector in Indonesia, one of which is cooperation in the cultivation of land, namely paron. Land cultivation cooperation has an important meaning in the development of the Indonesian agricultural sector, especially farmers in Guluk-guluk Village. This study aims to analyze the implementation of paron in the fiqih review of four schools. In this study using descriptive qualitative methods in which researchers are directly in the middle of the research subjects. The subjects of this study were those who were involved in the partnership, namely landowners and tenants. In order to make the research more relevant, the writer also conducted an interview with Islamic jurists. The results of the study showed that the practice of paron cooperation carried out by the people of Guluk-guluk Village was in accordance with Islamic law in terms of the contract, pillars and conditions of the muzaara'ah or mukhaabrah contract.